Pengaruh Gaya Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PR. DD Kabupaten Malang - Alvin Mauludi Setiawan; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis research aims to determine the relationship of leadership style, motivation, work discipline and employee performance on PR.DD Malang Regency. The population and sample used in this research were 76 employees at PR.DD Malang Regency. This research uses analysis tools to test the hypothesis, namely the classical assumption test, validity test, reliability test, multiple linear regression, the F-test, the t-test, and , the coefficient of determination (R2). The findings of this research indicate that leadership style, motivation and work discipline affect employee performance, this is evidenced by the t-test. Research findings using the F-test indicate that leadership style, motivation and work discipline together have a significant effect on employee performance at PR.DD Malang Regency. The result of the coefficient of determination (R2) test shows that employee performance in PR.DD is influenced by leadership style, motivation and work discipline by 48.89% and the model has passed the classical assumption test. Keywords : Leadership style, Motivation, Work Discipline and Employee Performance